(untitled) (De Musica, 2025)
In a debate held in «Music Analysis» between 2003 and 2004, two opposing positions, the formalist and the hermeneutic, coincide in the common need to define an idea of unity that does not nullify the value of the ‘particular’. In this context, Jonathan D. Kramer proposes the prolific concept of «coherence», which, however, lacks precise aesthetic connotations. My aim in this paper is to re-consider the concept of coherence from that of “Polyphony” as discussed by literary theorist Mikhail Bakhtin. In order to achieve my goal, I will take into consideration the suggested relationship (Hatten, 1994; Steyer, 1995; Cook, 2003) between aspects of Beethoven’s late style and Bakhtin’s perspective, and propose a ‘polyphonic’ analysis of the Beethoven’s Piano Sonata in A-flat major op. 110, in which the heterogeneity of material is conceived in a ‘multiple’ dimension of musical time that allows us to understand the latent references in the composition as signs of an inner dialog between movements.